Severe Open Fracture Tibiathe Relationship between External Fixation and Nonunion - Ab. Ghani, Sanusi Azni (2000)
A retrospective study was carried out from January 1997 to January 1999 to look into the rate of nonunion of severe open tibial fractures treated with external fixators. This study included 22 patients with 22 severe open diaphyseal tibial fractures of grade 11, lIlA and 111B seen within 1 years period in HUSM (Hospital Universiti Sains Malaysia), Kubang Kerian, Kelantan. The patients age ranged from 19 to 73 years (mean age of38.2 years). There were 19 males and 3 females. The mechanism of injury included 19 motorcycle accidents, one pedestrian-motorcycle accident, one motorvehicle accident and one logging injury. Two fractures were at the proximal third, eleven were middle third, eight were distal third and one was segmental. Clinical symptoms and plain radiographes were used to evaluate the union rate. The mean time interval from injury to application of external fixator was 18 hours. The mean duration of patient on external fixator was 66 days. The union rates was 13 weeks(6 patients). The duration on external fixator and time interval from injury to application of an external fixator also did not influence the union rate. Proximal third fracture healed faster than lower or middle third, however it was not statistically significant. Grade 11 Open tibial fracture healed faster than grade 111 A and grade 111 B. Highly comminuted fracture healed slower than simple fracture (Winquist 4 :28 weeks), however it was also not statistically significant.